Efektivitas Penerapan Standart Operating Procedure Melalui Seleksi Penggunaan Peralatan Bongkar Muat dan Alat Transportasi Pendukung di Pelabuhan Tanjung Emas, Semarang - Dwi Retnandari, Septina; Khaeroman, Khaeroman; Noviarianto, Noviarianto; Ilham Putranto, Angga (Jurnal Maritim Polimarin, 2024)
Research on the effectiveness of the implementation of Standard Operating Procedure (SOP) at Tanjung Emas Port, Semarang aims to find out how to improve the effectiveness of loading and unloading activities related to the selection of loading and unloading equipment and supporting transportation equipment. In addition, it also aims to determine supporting factors, inhibiting factors, strategies and the company's role in improving the effectiveness of the implementation of applicable SOP. As qualitative research with descriptive methods, data obtained from observation, interviews with respondents and keyperson, and documentary evidence. The results of this research are majority of companies who conduct loading and unloading products use appropriate and adequate supporting transportation equipment in accordance with applicable SOP. It can be concluded that the discipline in applying SOP when selecting loading and unloading equipment give impact to the effectiveness of loading and unloading process. The author suggests to pay attention to the age factor and maintenance of equipment and conduct a feasibility test before loading and unloading equipment is used to minimize risk